2019
DOI: 10.1155/2019/7623607
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Repeated Use of Donor Site for Noncultured Epidermal Cellular Grafting in Stable Vitiligo: A Retrospective Study

Abstract: Background Noncultured epidermal suspension (NCES) is a surgical technique which employs cellular grafting onto depigmented lesions. However, scarring and dyschromia at the donor site often occurs. Objective To assess the outcome of reusing the same donor site in subsequent sessions of NCES procedures. Methods Electronic records of vitiligo patients who had undergone two sessions of NCES procedures were retrospectively reviewed. Information on the first and second NCES was retrieved for analyses. Results A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…We analyzed a total of 117 unique studies with 8776 unique patients (eTable 1 in the Supplement), including 19 studies with 1631 patients in the punch grafting group, 10 studies with 718 patients in the thin skin grafting group, 29 studies with 2652 patients in the suction blister grafting group, 45 studies with 2209 patients in the noncultured epidermal cell suspension (NCES) group, 9 studies with 185 patients in the noncultured follicular cell suspension (NCFS) group, and 17 studies with 1381 patients in the cultured epidermal cell suspension (CES) group; 11 studies included more than 1 procedure type. The median follow-up duration was 7 (range, 2-108) months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed a total of 117 unique studies with 8776 unique patients (eTable 1 in the Supplement), including 19 studies with 1631 patients in the punch grafting group, 10 studies with 718 patients in the thin skin grafting group, 29 studies with 2652 patients in the suction blister grafting group, 45 studies with 2209 patients in the noncultured epidermal cell suspension (NCES) group, 9 studies with 185 patients in the noncultured follicular cell suspension (NCFS) group, and 17 studies with 1381 patients in the cultured epidermal cell suspension (CES) group; 11 studies included more than 1 procedure type. The median follow-up duration was 7 (range, 2-108) months.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the rate of repigmentation achieved by patients after 1 session of any surgical intervention included greater than 90% in 52.69% (95% CI, 46.87%-58.50%) in 106 studies with 6586 patients ( I 2 = 97.2%) (eFigure 2 in the Supplement); greater than 75% in 64.72% (95% CI, 59.52%-69.92%) in 100 studies with 3400 patients ( I 2 = 95.7%); and greater than 50% in 81.01% (95% CI, 78.18%-83.84%) in 92 studies with 5462 patients ( I 2 = 90.7%). According to the surgical intervention type, greater than 90% repigmentation was achieved in 72.08% (95% CI, 54.26%-89.89%) of patients undergoing thin skin grafting (670 patients in 8 studies), 61.68% (95% CI, 47.44%-75.92%) of patients undergoing suction blister grafting (2349 patients in 21 studies), 56.82% (95% CI, 48.93%-64.71%) of patients undergoing CES (1138 patients in 14 studies), 47.51% (95% CI, 37.00%-58.03%) of patients undergoing NCES (907 patients in 29 studies), 45.76% (95% CI, 30.67%-60.85%) of patients undergoing punch grafting (1354 patients in 11 studies), and 36.24% (95% CI, 18.92%-53.57%) of patients undergoing NCFS (160 patients in 8 studies) after 1 session of each surgery (eFigure 2 in the Supplement and Table 1). In our meta-regression analysis, for greater than 90% repigmentation, the estimate of the slopes for mean age of patients was −1.1418 ( P = .02); for the proportion of segmental vitiligo, 0.3047 ( P = .01); and for the proportion of treated lesions on the acral and joint areas, −0.4050 ( P = .002) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…As a clinical application of our study, we tried to reuse the donor area in both groups. We found that, the skin was tough in case of TG, and obtaining the graft was very difficult in contrast to the report by 36 . In their retrospective study, it was not mentioned whether they had used an ultrathin partial‐thickness epidermal cut to obtain the Thiersch grafts.…”
Section: Discussionmentioning
confidence: 64%